2019
DOI: 10.1016/j.brat.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Positive cognitive behavior therapy in the treatment of depression: A randomized order within-subject comparison with traditional cognitive behavior therapy

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 57 publications
3
40
0
1
Order By: Relevance
“…Overall outcomes were superior in the complete-case analyses relative to the imputed data set on all variables (large versus medium pre-post effect sizes), but critically the relative magnitude of symptom versus wellbeing repair was the same in both sets of analyses. This result broadly mirrors findings in previous trials that have included classic CBT as a comparator for novel positive psychology or wellbeing interventions (Chaves et al 2017;Geschwind et al 2019;Fava et al 1998a;Fava et al 2005) and also is consistent with meta-analytic findings that CBT and drug treatments for depression have a bigger effect on symptoms than quality of life (Hofmann et al 2017). It extends them by directly comparing wellbeing and symptom deficits in a large clinical sample, giving greater precision to the estimates observed.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Overall outcomes were superior in the complete-case analyses relative to the imputed data set on all variables (large versus medium pre-post effect sizes), but critically the relative magnitude of symptom versus wellbeing repair was the same in both sets of analyses. This result broadly mirrors findings in previous trials that have included classic CBT as a comparator for novel positive psychology or wellbeing interventions (Chaves et al 2017;Geschwind et al 2019;Fava et al 1998a;Fava et al 2005) and also is consistent with meta-analytic findings that CBT and drug treatments for depression have a bigger effect on symptoms than quality of life (Hofmann et al 2017). It extends them by directly comparing wellbeing and symptom deficits in a large clinical sample, giving greater precision to the estimates observed.…”
Section: Discussionsupporting
confidence: 87%
“…Alternatives to Wellbeing Therapy as staging treatments are also starting to emerge. For example, Geschwind et al (2019) demonstrate a large pre-post wellbeing effect size for CBT followed by a positive CBT protocol (albeit this wellbeing improvement was smaller than that observed for symptom relief).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this clinical trial, clients received both traditional CBT (based on Beck et al, 1979) and positive CBT (Bannink, 2012) in two blocks of eight sessions each, with the order of blocks randomized (i.e., first traditional CBT, then positive CBT, or vice versa). In the analysis of questionnaire data belonging to this study (Geschwind et al, 2019), positive CBT resulted in a stronger reduction of depression during the second phase of treatment, whereas the reduction of depressive symptoms stagnated in traditional CBT. Independent of treatment phase, positive CBT was associated with more clinically significant change than traditional CBT.…”
Section: Positive Cbtmentioning
confidence: 70%
“…Scale ranges: BPD traits 0-10, HAP 8-40, LAP 3-15, NA (LN-transformed) 2.30-3.69, NA 10-50. (Craske et al, 2019;Dunn, 2019;Geschwind, Arntz, Bannink, & Peeters, 2019;Sewart et al, 2019). Reflecting on the Best Possible Self (rather than recalling positive memories) may be a particularly effective way of stimulating positive affect for people with heightened psychopathology, given that a recent study found that adopting a more analytic, reflective perspective (rather than merely recounting positive events) led to increased improvements in both PA and NA for individuals with major depression (Pfaltz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%